Delineation of the phenotype of MED17-related disease in Caucasus-Jewish families. (May 2021) - Fattal-Valevski, Aviva; Ben Sira, Liat; Lerman-Sagie, Tally; Strausberg, Rachel; Bloch-Mimouni, Aviva; Edvardson, Simon; Kaufman, Rami; Chernuha, Veronika; Schneebaum Sender, Nira; Heimer, Gali; Ben Zeev, Bruria
Abstract: Background: and Purpose: Postnatal progressive microcephaly, with seizures and brain atrophy (OMIM # 613668) is a rare disorder caused by a homozygous founder missense mutation c.1112T>C (p.L371P) in the MED17 gene on chromosome 11 that was identified in 2010 in Caucasus Jewish families. The present study aimed to delineate the phenotype and developmental outcomes in patients diagnosed with this mutation to date. Methods: We conducted a medical charts review to collect the clinical, laboratory and neuroimaging findings in patients from several unrelated families of Caucasus-Jewish origin, who were diagnosed with the same homozygous c.1112T>C MED17 mutation. Results: The study cohort, including the previously reported patients, comprised 10 males and 5 females from 11 families. All subjects had at birth a normal head circumference, which steeply declined to -6SD within a few months. None of the patients achieved developmental milestones. All patients had progressive spasticity and were wheelchair bound due to spastic quadriplegia. All of them eventually developed profound intellectual disability. Epilepsy of varied severity was present in all patients. Most patients required enteral feeding due to aspirations. Eight patients died before puberty (age range 2–13 years). Brain MRI showed marked cerebral atrophy and early prominent cerebellar atrophy (vermian > hemispheres) accompanied by pontine ventral flattening. Conclusions: The founder c.1112T>C mutation in MED17 gene is expressed by a unique and homogeneous clinical phenotype with distinctive MRI findings. This mutation should be considered in patients of Caucasus-Jewish ancestry presenting with clinical features and a MRI pattern of progressive cerebral and cerebellar atrophy. Highlights: MED17-related disorders present with different severity depending on the underlying gene mutations. Founder c.1112T>C mutation in MED17 gene in Caucasus Jews is expressed by infantile cerebral and cerebellar atrophy. Main clinical features are progressive microcephaly, spastic quadriplegia and epilepsy. MRI shows early progressive cerebral/cerebellar atrophy and flattening of pons. Nearly all individuals have severe intellectual disability and shortened life expectancy.